Immunization strategies for the prevention of pneumovirus infections. (April 2007) - Bennett, Nicholas; Ellis, John; Bonville, Cynthia; Rosenberg, Helene; Domachowske, Joseph
Pneumoviruses, which are viruses of the family Paramyxoviridae, subfamily Pneumovirinae, are pathogens that infect the respiratory tract of their host species. The human pneumovirus pathogen, human respiratory syncytial virus (RSV), has counterparts that infect cows (bovine RSV), sheep (ovine RSV), goats (caprine RSV) and rodents (pneumonia virus of mice). Each pneumovirus is host specific and results in a spectrum of disease, ranging from mild upper-respiratory illness to severe bronchiolitis and pneumonia with significant morbidity and mortality. Given the public health burden caused by human RSV and the concomitant agricultural impact of bovine RSV, these two viruses are considered as prime targets for the development of safe and effective vaccines. In this review, we describe the strategies used to develop vaccines against human and bovine RSV and introduce the pneumonia virus mouse model as a novel and invaluable tool for preclinical studies and new vaccine strategies.